Kegagalan Perawatan Restorasi Plastis Komposit Kelas IV oleh Mahasiswa Pendidikan Profesi Kedokteran Gigi di RSGMP UNEJ - Diajeng Gusti Purnama Az. Zahra (Fakultas Kedokteran Gigi, 2025)
Introduction: Teeth have four main functions, namely the function of mastication, aesthetic function, speech function, and the function of protecting the supporting tissues. Aesthetic problems in anterior teeth are often experienced by children and adults which can be caused by caries and fractures. The management of caries and fractures is with class IV restoration treatment with composite resin material because it has a tooth color so that it can restore aesthetic function. Patients are given IEC by the operator after treatment is complete to increase the longevity of the restoration, if the patient does not comply with the IEC that has been given, it is possible for composite restoration treatment failure. Objective: The aim of this research is to determine the type and the percentage of failure of class IV composite plastic restoration treatment which is influenced by the patient's inability to carry out the IEC that has been given by dental professional education students at RSGMP Jember University. Method: This study used descriptive research methods. In this study, patients were recall to be examined for the results of class IV composite restorations that had been carried out by dental professional education students 6 months ago at Jember University RSGMP. The results obtained in the form of qualitative data, namely questionnaires and subjective, objective and radiographic examinations which were then tabulated and analyzed. Result: The results of the research showed that 15 subjects experienced treatment failure and 11 subjects experienced treatment success. failure of class IV composite restorations that can be caused by patient non compliance with IEC that has been given by dental professional education students at Jember University RSGMP is fracture restorations. Conclusion: The conclusion of this research is that the type and the percentage of failure of class IV composite plastic restoration treatment at RSGMP University of Jember.assay. Enzyme kinetics assays were conducted using Pocine Pancreatic Elastase (PPE) and varying concentrations of the N-Succinyl-Ala-Ala Ala-p-nitroanilide (SANA) substrate. The results demonstrated successful purification of SLPIc, evident by a single ~32-33 kDa protein band in the elution fractions with 307,5 until 370 mM imidazole. Kinetic analysis showed that SLPIc (66,5 μg/mL) decreased the Vmaks of PPE from 1,397 to 1,163 nmol/min and increased the Km from 1,501 to 2,322 mM, indicating a mixed-type inhibition mechanism. These findings highlight the therapeutic potential of SLPIc in mitigating tissue damage caused by excessive protease activity during myocardial infarction
Reaploud Repository February 2026_Hasyim
Keywords: restoration failure; composite restoration; anterior teeth; failure rate; IEC